Pengaruh Kecerdasan Emosional dan Dukungan Sosial terhadap Resiliensi Akademik Doktoral Jawa Barat - Ayuni Yasmin Adianti Suharta; Suci Nugraha (Jurnal Riset Psikologi, 2026)
Abstract. Doctoral students face various academic and psychological challenges, including research demands, publication pressure, and role conflicts in their personal and professional lives. These conditions require academic resilience, defined as the ability to adapt and persist under academic stress. This study aimed to examine the influence of emotional intelligence and social support on academic resilience among doctoral students in West Java. A quantitative approach with a cross-sectional survey design was employed, involving 120 active doctoral students from several institutions. Data were collected using the Assessing Emotional Scale (AES), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Academic Resilience Scale (ARS-30). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that emotional intelligence and social support have a positive and significant effect on academic resilience. An R-Square value of 0.840 shows that both variables explain 84% of the variance in academic resilience. These findings highlight the importance of strengthening emotional intelligence and social support to enhance doctoral students’ academic success. Abstrak. Mahasiswa program doktoral menghadapi berbagai tantangan akademik dan psikologis, seperti tuntutan penelitian, tekanan publikasi, serta konflik peran dalam kehidupan pribadi dan profesional. Kondisi tersebut memerlukan ketahanan akademik, yaitu kemampuan untuk beradaptasi dan bertahan dalam menghadapi tekanan akademik. Penelitian ini bertujuan menganalisis pengaruh kecerdasan emosional dan dukungan sosial terhadap ketahanan akademik mahasiswa doktoral di Jawa Barat. Penelitian menggunakan pendekatan kuantitatif dengan desain survei cross-sectional terhadap 120 mahasiswa program doktoral aktif dari berbagai institusi. Data dikumpulkan menggunakan Assessing Emotional Scale (AES), Multidimensional Scale of Perceived Social Support (MSPSS), dan Academic Resilience Scale (ARS-30), kemudian dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) melalui SmartPLS 4. Hasil penelitian menunjukkan bahwa kecerdasan emosional dan dukungan sosial berpengaruh positif dan signifikan terhadap ketahanan akademik. Nilai R-Square sebesar 0,840 menunjukkan bahwa kedua variabel mampu menjelaskan 84% variasi ketahanan akademik. Temuan ini menegaskan pentingnya pengembangan kecerdasan emosional dan dukungan sosial untuk meningkatkan keberhasilan akademik mahasiswa program doktoral.